2019
DOI: 10.3389/fcomm.2018.00063
|View full text |Cite
|
Sign up to set email alerts
|

“Be Worried, be VERY Worried:” Preferences for and Impacts of Negative Emotional Climate Change Communication

Abstract: While communication experts largely recommend avoiding climate change messages that create negative emotional states, little is known regarding how members of the public use emotions in their own communication about climate change. Given the important role individuals can play in addressing climate change via their interpersonal communication, it is important to understand preferences for using or avoiding communication framed with negative emotions, and their ultimate impact on taking action to address climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…It may be that fear does not trigger consideration, but rather apathy for the future consequences of climate change. A recent study that tested preferences for and impacts of three negative emotions (fear, sadness, and anger) in comparison to messages framed without emotion, found that people generally preferred messages framed without emotion (Bloodhart et al 2018). Thus, an increasing recommendation found in academic research and literature is that participants prefer non-emotional messages to modi ed emotional messages about climate change (Bloodhart et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that fear does not trigger consideration, but rather apathy for the future consequences of climate change. A recent study that tested preferences for and impacts of three negative emotions (fear, sadness, and anger) in comparison to messages framed without emotion, found that people generally preferred messages framed without emotion (Bloodhart et al 2018). Thus, an increasing recommendation found in academic research and literature is that participants prefer non-emotional messages to modi ed emotional messages about climate change (Bloodhart et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there is increasing debate on the effects of targeting speci c emotions on motivating or inhibiting public engagement with climate change, especially for the emotions of fear and hope (Ojala 2012;Lemanski and Villegas 2019). For example, a limited series of studies investigating actual behavior in response to fear appeals showed that the results were mixed (Hine and Gifford, 1991;Bloodhart et al 2018). Some researchers pointed out that instilling fear in people might cause avoidance and reductions in personal e cacy, whereas making people feel hopeful caused increased e cacy and engagement (O'Neill and Nicholson-Cole 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, anger toward insufficient environmental protection or the waste of water acts as an activator of proenvironmental commitment [59,60]. However, perceptions of the global water crisis derived from climate change may also lead to just the opposite: if the problem is perceived as a "lost battle", then the negative emotions elicited-fear, powerlessness-may lead people to also lose their motivation and feel unable to deal with this challenge [61].…”
Section: The Emotional Component: Negative Emotionsmentioning
confidence: 99%
“…Milton (2002) suggests that the motivating force of an argument lies in its emotional impact, and that we need to recognise this, as well as its logic, if we are to understand how it moves people to action. Despite assumptions that negative emotions should be avoided, emotional messages conveying sadness or anger about climate change can be persuasive especially when they reflect the feelings of message recipients (Bloodhart, Swim, and Dicicco 2019). Elsewhere, positive emotional messages about the environment can be more effective than informational messages in arousing effects at a personal level, suggesting that socially desirable public policies should be promoted in ways that feature emotional appeals (Hoewe and Ahern 2017).…”
Section: Effective and Affective Framing Of Threatened Bird Conservationmentioning
confidence: 99%
“…If conservation practitioners do not convey empathy for what they wish to conserve, they may be missing a vital opportunity to inspire the public to participate in conservation action. Public messages advocating for threatened bird conservation could be framed in positive ways that arouse emotions, since arguments motivate best when they induce feelings like hope, satisfaction, pleasure, excitement, interest, anger, sadness or distress (Milton 2002;Knight 2013;Bloodhart, Swim, and Dicicco 2019). Such framing strategies need to emphasise human agency (e.g.…”
Section: Effective and Affective Framing Of Threatened Bird Conservationmentioning
confidence: 99%